1996
DOI: 10.1093/jee/89.4.990
|View full text |Cite
|
Sign up to set email alerts
|

Chlorosis, Photosynthesis, and Transpiration of Azalea Leaves After Azalea Lace Bug (Heteroptera: Tingidae) Feeding Injury

Abstract: Feeding injury caused by nymphs, males and females of the azalea lace bug, Steplwnitis pyrioides (Scott), reduced rates of photosynthesis and transpiration in 'Delaware Valley White' azalea, RllOdodendron mucronatulIl leaves. Females caused substantially more leaf feeding injury than males or nymphs. S. pyrioides was observed to insert stylets through stomata on the lower leaf surface and to feed almost entirely on upper palisade parenchyma tissue by piercing and removing cell contents. Lace bug feeding increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 11 publications
4
66
1
3
Order By: Relevance
“…Losses of chlorophyll content due to insect herbivory have been quantified in other hemipterans using similar chlorophyll analyses. Other researchers (Buntin et al 1996;Morales et al 2002;Goławska et al 2010) have explored the leaves of stressed plants apparently with less synthesised chlorophyll content, and these changes may be part of the adaptive responses. Chlorophyll a and b concentrations can be significantly higher in non-infested leaves with both short and long infestations of plants compared to the infested ones (Goławska et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Losses of chlorophyll content due to insect herbivory have been quantified in other hemipterans using similar chlorophyll analyses. Other researchers (Buntin et al 1996;Morales et al 2002;Goławska et al 2010) have explored the leaves of stressed plants apparently with less synthesised chlorophyll content, and these changes may be part of the adaptive responses. Chlorophyll a and b concentrations can be significantly higher in non-infested leaves with both short and long infestations of plants compared to the infested ones (Goławska et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…They confirmed that the permanent impairment of photosynthetic photochemistry was restricted to the damaged areas on the leaf. Buntin et al (1996) showed that feeding injury caused by Stephanitis pyrioides (Scott) reduced the chlorophyll content and adversely affected net leaf photosynthesis and transpiration in azalea. The feeding of Bemisia tabaci Gennadius reduced the leaf photosynthesis in tomato leaves by decreasing the content and photosynthetic capacity of chlorophyll (Buntin et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Shuster et al (1980) showed tolerance of strawberry cultivars to two spotted spider mites and concluded that content of chlorophyll in tolerant cultivars is not significantly decreased despite the high density of the pest. Buntin et al (1996) by studying the effect of pear lace bug damage on photosynthetic rate and leaf's gas exchange concluded that the effects of pear lace bug feeding on parenchyma tissue and causing damage are increased stomatal resistance and limiting of gas exchange and decreased leaf chlorophyll rate.…”
Section: Archives Of Phytopathology and Plant Protection 1145mentioning
confidence: 99%
“…There are more studies on Stephanitis pyrioides (Scott), the most important pest of azaleas (Braman et al 1992;Shrewsbury and Raupp 2000;Klingeman et al 2000aKlingeman et al , b, 2001aStewart et al 2002) and some other species, like Corythucha sp., (Braman and Pendley 1993;Rédei et al 2004;Bernardinelli 2006) in the USA and Eastern Europe. Buntin et al (1996) observed that S. pyrioides insert stylets through stomata on the lower leaf surface and feed almost entirely on upper palisade parenchyma tissue by piercing and removing cell contents. Forecasting models based on heat accumulation units should be developed for S. pyri like those reported for the azalea lace bug by Braman et al (1992).…”
Section: Introductionmentioning
confidence: 99%